A Pilot Study of Four Cultural Touch-Screen Games - Wang, L.; Champion, Erik (ACM, 2011)
Four simple single-player games (based on the "Four Arts" of traditional Chinese culture) have been designed in Flash for a touch-screen display. The aim is to allow players to experience a digital interactive recreation of traditional Chinese culture, in order to understand features of traditional Chinese culture and related philosophical concepts such as Daoism. To evaluate the effectiveness of the design, a pilot study was conducted with twelve participants, six were Chinese speaking and six were not. The pilot study suggest that there are differences between Chinese and non-Chinese users in perceived notions of authenticity and ease of use and it has provided us with ideas on how to improve both the games and the evaluation.